2005
DOI: 10.1542/peds.2005-0937
|View full text |Cite
|
Sign up to set email alerts
|

All-Terrain Vehicle–Related Nonfatal Injuries Among Young Riders: United States, 2001–2003

Abstract: ABSTRACT. Background. All-terrain vehicles (ATVs) have gained in popularity in recent years, and this rise in use has been accompanied by increases in the number of ATV-related injuries. Because children often lack the physical strength, cognitive abilities, and fine motor skills to operate ATVs properly, their risk for injury is greater. Furthermore, most children ride adult-sized ATVs.Objectives. To estimate the numbers and rates of ATV-related nonfatal injuries to riders aged <15 years who were treated in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 10 publications
0
25
1
Order By: Relevance
“…Recent studies illustrate the ongoing and serious nature of ATV crashes. 10,11,15 One report showed that pediatric ATV-related traumas were associated with more interhospital transfers and higher injury severity scores than other trauma admissions. 15 …”
Section: Discussion Pediatric Fatalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies illustrate the ongoing and serious nature of ATV crashes. 10,11,15 One report showed that pediatric ATV-related traumas were associated with more interhospital transfers and higher injury severity scores than other trauma admissions. 15 …”
Section: Discussion Pediatric Fatalitiesmentioning
confidence: 99%
“…2 The high risk for death and injury among youth is likely attributable to a number of factors, including physical and mental immaturity, lack of training and experience, operating adult-size machines, riding on roadways, not wearing a helmet, and carrying or being a passenger. [3][4][5][6][7][8][9][10][11][12] According to the Consumer Product Safety Commission (CPSC), youth ,16 years of age have represented approximately one-quarter of all deaths and one-third of all US ATV-related injuries. 13 More than 40% of these pediatric deaths were children ,12 years of age.…”
mentioning
confidence: 99%
“…Although much of the focus has been on the social costs of fatalities, nonfatal injuries are a major concern as well and deserve attention. While an explanation is not totally clear, the decline in ATV-related injuries in 2008 and 2009 as shown in Figure 1 may be related to decreased sales of new ATVs during the economic recession of the mid-2000s [3]. CPSC is still collecting data on the deaths that have occurred since 2009.…”
Section: Introductionmentioning
confidence: 99%
“…4 There were also ∼360 000 emergency department (ED) visits for children younger than 15 years old for ATV-related injuries between 2001 and 2010. 5,6 SxSs were involved in 335 fatalities and 506 injuries over a similar time frame, with drivers younger than 16 years old contributing to >50% of the incidents. 1,2 The significant morbidity and mortality associated with the use of ORVs by children has led to medical societies, legislators, and health care providers advocating for federal safety standards and injury prevention legislation.…”
mentioning
confidence: 99%
“…1,2 The significant morbidity and mortality associated with the use of ORVs by children has led to medical societies, legislators, and health care providers advocating for federal safety standards and injury prevention legislation. 3,5,7,8 ORV injury prevention efforts began in the late 1980s when the Consumer Product Safety Commission (CPSC) and members of the ATV industry entered a 10-year consent decree that included the banning of 3-wheeled vehicles, a free nationwide training program offered to purchasers of new ATVs, and age recommendations for ATV use. 4,9 The American Academy of Pediatrics (AAP) also became involved in 1987 with its first policy statement calling for several safety measures, including the prohibition of ATV use by children younger than 14 years old.…”
mentioning
confidence: 99%